IRF2BP2 Mutation Is Associated with Increased STAT1 and STAT5 Activation in Two Family Members with Inflammatory Conditions and Lymphopenia - Maaria Palmroth; Hanna Viskari; Mikko R. J. Seppänen; Salla Keskitalo; Anniina Virtanen; Markku Varjosalo; Olli Silvennoinen; Pia Isomäki (MDPI AG, 2021)
Interferon regulatory factor 2 binding protein 2 (IRF2BP2) is a transcriptional coregulator that has an important role in the regulation of the immune response. IRF2BP2 has been associated with the Janus kinase (JAK)-signal transducers and activators of transcription (STAT) pathway, but its exact role remains elusive. Here, we identified a novel clinical variant, IRF2BP2 c.625_665del, from two members of a family with inflammatory conditions and investigated the function of IRF2BP2 and c.625_665del mutation in JAK-STAT pathway activation and inflammatory signaling. The levels of constitutive and cytokine-induced phosphorylation of STATs and total STAT1 in peripheral blood monocytes, T cells, and B cells from the patients and four healthy controls were measured by flow cytometry. Inflammation-related gene expression was studied in peripheral blood mononuclear cells using direct digital detection of mRNA (NanoString). Finally, we studied the relationship between IRF2BP2 and STAT1 activation using a luciferase reporter system in a cell model. Our results show that patients having the IRF2BP2 c.625_665del mutation presented overexpression of STAT1 protein and increased constitutive activation of STAT1. In addition, interferon-induced JAK-STAT signaling was upregulated, and several interferon-inducible genes were overexpressed. Constitutive phosphorylation of STAT5 was also found to be upregulated in CD4+ T cells from the patients. Using a cell model, we show that IRF2BP2 was needed to attenuate STAT1 transcriptional activity and that IRF2BP2 c.625_665del mutation failed in this. We conclude that IRF2BP2 has an important role in suppressing immune responses elicited by STAT1 and STAT5 and suggest that aberrations in IRF2BP2 can lead to abnormal function of intrinsic immunity.